2016
DOI: 10.1002/ajh.24342
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HLA‐Mismatch in Unrelated Donor Hematopoietic Stem Cell Transplantation: A Meta‐Analysis

Abstract: The magnitude of risk associated with 9/10 mismatched unrelated donor (MMURD) hematopoietic stem cell transplantation and that of mismatches at the individual HLA loci remain unclear. We performed a metaanalysis to assess the difference in clinical outcomes between matched unrelated donor (MUD) and MMURD transplantation. A comprehensive search of Medline and Embase for manuscripts regarding transplantation outcomes in primarily adult patients with hematologic malignancies was performed. The pooled effect estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 29 publications
4
31
0
Order By: Relevance
“…Most recently, one meta-analysis demonstrated that 9/10 HLA matching had a higher risk of mortality, compared with 10/10 matching, with hazard ratio of 1.27 (95% CI, 1.12 to 1.45; P < .001) [56], which was similar to ours (HR, 1.31; 95% CI, 1.14 to 1.50; P = .001). In addition, the risk for individual HLA allele mismatches was similar with it in our stratified analyses.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Most recently, one meta-analysis demonstrated that 9/10 HLA matching had a higher risk of mortality, compared with 10/10 matching, with hazard ratio of 1.27 (95% CI, 1.12 to 1.45; P < .001) [56], which was similar to ours (HR, 1.31; 95% CI, 1.14 to 1.50; P = .001). In addition, the risk for individual HLA allele mismatches was similar with it in our stratified analyses.…”
Section: Discussionsupporting
confidence: 83%
“…Despite there are several guidelines published, evidence-based recommends have been absent so far [5255]. Most recently, a published meta-analysis assess the impact of HLA-DPB1 allele mismatches on overall survival of patients receiving unrelated-donor HCT [56]. Other important end points were not mentioned, and many studies with large populations were not included in the review.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of 7 retrospective studies comparing 10/10 MUD and 9/10 MUD alloHSCT showed a 27% increased risk of mortality for recipients of a 9/10 MUD. 23 Here, a similarly increased risk (25%) was found when comparing 9/10 MUDs with 10/10 MUDs in patients with poor-risk AML in CR1. These results suggest that transplants using 9/10 MUD may be followed by more stringent prevention of GVHD to limit NRM.…”
Section: Discussionsupporting
confidence: 52%
“…As the number of available sibling donors declines due to smaller family size in recent decades and potential issues related to donor eligibility in older siblings, transplant centers continue to rely heavily on unrelated donors and cord blood units (CBUs). Canadian transplant centers typically prefer allele matching of prospective donors at HLA‐A, ‐B, ‐C, ‐DRB1, and ‐DQB1 loci, with the hope of identifying 10 of 10 HLA‐matched donors . While HLA match level between donor/recipient pairs is considered to be the dominant factor in the selection of unrelated donors, the extent to which additional factors such as sex and donor age influence donor choice remains unclear and the impact of patient ethnicity on donor matching in Canada is unknown.…”
mentioning
confidence: 99%
“…Canadian transplant centers typically prefer allele matching of prospective donors at HLA-A, -B, -C, -DRB1, and -DQB1 loci, with the hope of identifying 10 of 10 HLA-matched donors. 3 While HLA match level between donor/recipient pairs is considered to be the dominant factor in the selection of unrelated donors, 4 the extent to which additional factors such as sex and donor age influence donor choice remains unclear and the impact of patient ethnicity on donor matching in Canada is unknown. While OneMatch (OM) search specialists can assist in allogeneic search strategies, donor selection is ultimately the responsibility of Canadian transplant centers.…”
mentioning
confidence: 99%